Periconceptional and Prenatal Exposure to Metals and Extracellular Vesicle and Particle miRNAs in Human Milk: A Pilot Study - Caitlin G. Howe; David A. Armstrong; Meghan E. Muse; Diane Gilbert-Diamond; Jiang Gui; Anne G. Hoen; Thomas J. Palys; Roxanna L. Barnaby; Bruce A. Stanton; Brian P. Jackson; Brock C. Christensen; Margaret R. Karagas (Exposure and Health, 2023)

Quantifying the Effects of Floating Oyster Aquaculture on Nitrogen Cycling in a Temperate Coastal Embayment - Micheline S. Labrie; Miles A. Sundermeyer; Brian L. Howes (Estuaries and Coasts, 2023)

Modelling the Spatial Distribution of Oyster (Crassostrea virginica) Biodeposits Settling from Suspended Aquaculture - Micheline S. Labrie; Miles A. Sundermeyer; Brian L. Howes (Estuaries and Coasts, 2022)

Insula and the Immune System: More than mere Co-existence? - Panagiotis Kerezoudis; Charles L. Howe; Long-Jun Wu; Brian N. Lundstrom; Jamie J. Van Gompel (Neuroscience Bulletin, 2022)

Numbers matter: how irruptive bark beetles initiate transition to self-sustaining behavior during landscape-altering outbreaks - Michael Howe; Kenneth F. Raffa; Brian H. Aukema; Claudio Gratton; Allan L. Carroll (Oecologia, 2022)

Impacts of zebra mussels (Dreissena polymorpha) on isotopic niche size and niche overlap among fish species in a mesotrophic lake - Alexandra L. Morrison; Mary A. Thelen; Sarah E. Howe; Kyle D. Zimmer; Brian R. Herwig; David F. Staples; Margaret C. McEachran (Biological Invasions, 2021)

Systematic Review and Meta-Analysis Toward Synthesis of Thresholds of Ocean Acidification Impacts on Calcifying Pteropods and Interactions With Warming - Nina Bednaršek; Richard Alan Feely; Ella L. Howes; Brian P. V. Hunt; Faycal Kessouri; Pablo León; Silke Lischka; Amy E. Maas; Karen McLaughlin; Nikolay P. Nezlin; Martha Sutula; Stephen B. Weisberg (Frontiers in Marine Science, 2019)

Regional Forcing by Light on Dissolved Oxygen Levels in Shallow Temperate Estuaries - Anna M. Sawabini; David R. Schlezinger; Miles A. Sundermeyer; Brian L. Howes (Estuaries and Coasts, 2015)

Salt marshes and eutrophication: An unsustainable outcome - R. Eugene Turner; Brian L. Howes; John M. Teal; Charles S. Milan; Erick M. Swenson; Dale D. Goehringer‐ Tonerb (Limnology and Oceanography, 2009)
Most plant production by emergent coastal marshes occurs belowground. This belowground production adds to the accumulation of organic matter sustaining salt marshes as sea level rises, thus preventing excessive flooding, eventual plant death, and habitat loss. The ubiquitous nutrient enrichment of coastal salt marshes stimulating aboveground plant growth may result in higher rates of inorganic matter accumulation that compensates for marsh flooding caused by sea level rise. Results from several short‐term experiments, however, demonstrate that root and rhizome biomass and carbon accumulation is reduced with nutrient enrichment, suggesting that eutrophication of coastal waters may not be a compensatory counterbalance to the effects of global sea level rise on salt marshes. We show that the net effects of 36 yr of nutrient enrichment in replicated field experiments do not lead to higher organic or inorganic accumulation. Enrichment reduces organic matter belowground and may result in a significant loss in marsh elevation equivalent to about half the average global sea level rise rates. Sustaining and restoring coastal emergent marshes is more likely if they receive less, not more, nutrient loading.

Spatial Patterns of Macrobenthic Communities in Shallow-Water Tidal Embayments and Their Association with Environmental Factors - Yong Q. Tian; Jianjun Wang; John A. Duff; Brian L. Howes; Angeliki Evgenidou (Environmental Management, 2009)